PENGARUH LATIHAN HURDLE JUMP (LOMPAT RINTANGAN) TERHADAP PENINGKATAN KEMAMPUAN KECEPATAN TENDANGAN SABIT KEGIATAN EKSTRAKURIKULER PENCAK SILAT PADA SISWA PUTRA SMP NEGERI 19 PALEMBANG - Hikmah Lestari (JURNAL PENDIDIKAN ROKANIA, 2017)
This study entitled "The effects of exercise hurdle jumpterhadap increase the speed capabilities of the crescent kick martial arts extracurricular activities malestudent SMP Negeri 19 Palembang". The problem of this research is the influence of exercise hurdle jumpterhadap increase the speed capabilities of the crescent kick martial arts extracurricular activities students of SMP Negeri 19 Palembang? This study aims to determine whether there are effects of exercise urdle jumpterhadap increase the speed capabilities of the crescent kick martial arts extracurricular activities male student SMP Negeri 19 Palembang. Sample of this research is the male student extracurricular martial arts SMP 19 Palembang, amounting to 40 people. This research used experimental research consists of twoclasses, namely the class of instruments and control and data retrieved through the initial test (pre-test) and final test (post-test). Treatment given instrument group exercise hurdle jump 6 weeks with the number of meetings exercise 18 times. After doing the exercises and do post-test obtained an increase in the mean of the increase in the experimental group and the control group by 2.3 and 0.9. As well as the results of hypothesis testing showed the value of t is greater than t table ie 7.2196> 1,68 so Ha Ho accepted and rejected. This shows that there are significant in this study thus Ha Ho accepted and rejected. These results indicate that the hurdle jump training methods to give effect to increase the speed capabilities of the crescent kick martial arts extracurricular activities male student SMP Negeri 19 Palembang.